MODELLING IMPACT OF SOCIAL MEDIA ON MARRIAGE PRACTICES IN INDIA: A TISM APPROACH - Vinod; Nagar, Rajeev (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the influence of social media on contemporary marriage practices using the Total Interpretive Structural Modelling (TISM) approach. With the rise of social media platforms, traditional marriage customs have experienced significant transformations, altering not only how couples meet and communicate but also impacting societal norms, expectations, and rituals surrounding marriage. By employing TISM, this study systematically identifies, categorizes, and models the key factors that drive these changes, offering a structured understanding of their interrelationships. The research is based on an extensive review of literature and insights from subject matter experts, focusing on how social media reshapes matchmaking, wedding planning, relationship dynamics, and community involvement in marriages. The findings reveal both positive and negative implications of social media on marriage practices, highlighting the complexities of modern relationships influenced by digital interaction. This study provides a valuable framework for researchers and practitioners to further examine the evolving role of social media in shaping cultural practices.